1992
DOI: 10.1017/s0021932000020034
|View full text |Cite
|
Sign up to set email alerts
|

Some determinants of population variation in cortisol levels in a British urban community

Abstract: SummaryUrinary cortisol excretion rates were determined from three urine samples given over 2 days, a rest day and a working day, by 51 men and 50 women. Each subject also completed a questionnaire relating to life style factors and to perceived levels of stress, busyness and happiness on each day. In men, an association between raised cortisol and high levels of stress was found. In women, high levels of busyness were associated with low cortisol excretion rates. The subjective experiences measured accounted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…3 Assessment of physiological markers of stress can help surmount some of these obstacles by providing a quantitative measure of "stress response." Previous anthropological work has successfully linked stressors to differences in blood pressure (Dressier 1991;Janes 1990;McGarvey and Schendel 1986), catecholamine and cortisol levels (Brown 1981(Brown , 1982Flinn and England 1995;Pollard et al 1992;Schmitt et al 1995), and cell-mediated immune function ( McDade 2001, in press;. These markers are "objective" in that they are beyond the conscious control of the study participants and are therefore not vulnerable to recall or observer bias.…”
Section: Defining and Measuring Stressmentioning
confidence: 99%
“…3 Assessment of physiological markers of stress can help surmount some of these obstacles by providing a quantitative measure of "stress response." Previous anthropological work has successfully linked stressors to differences in blood pressure (Dressier 1991;Janes 1990;McGarvey and Schendel 1986), catecholamine and cortisol levels (Brown 1981(Brown , 1982Flinn and England 1995;Pollard et al 1992;Schmitt et al 1995), and cell-mediated immune function ( McDade 2001, in press;. These markers are "objective" in that they are beyond the conscious control of the study participants and are therefore not vulnerable to recall or observer bias.…”
Section: Defining and Measuring Stressmentioning
confidence: 99%
“…There is no doubt that unpleasant features of work correlate with pejorative psychological mood (Karasek, 1979), but the connections between work characteristics and/or mood and cortisol are problematic. A recent investigation of a group of Oxford City residents, mainly of upper social class (Pollard et al, 1992(Pollard et al, ,1994, found few cortisol associations, though reported "business" was negatively correlated in women. In a more detailed investigation of the psychology of job experience on much the same population, there was a systematic negative association in both men and wromen between cortisol output and job strain, that is, exactly opposite from what is hypothe-sized.…”
Section: Lagos (Nigeria) Manual Workers Seattle ( U S a ) American mentioning
confidence: 99%
“…On the other hand, patients treated with glucocorticoids suffer from sleeplessness associated with arousal and activation [6,7], and also elevated endogenous cortisol levels have been reported to be related to insomnia and arousal [15][16][17]. In stress studies performed in healthy subjects, states of negative emotionality are reported to be associated with increases in endogenous cortisol levels [e.g., [18][19][20], whereas the results with respect to positive emotionality are controversial -positive mood changes reported by Brown et al [18]; no relationships reported by Hennig et al [1] and Clark et al [21].…”
Section: Introductionmentioning
confidence: 99%